1998
DOI: 10.1136/ard.57.11.697
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase activity in equine synovial fluid: influence of age, osteoarthritis, and osteochondrosis

Abstract: Objective-To investigate the influence of age, osteoarthritis (OA), and osteochondrosis (OC) on the matrix metalloproteinase (MMP) activity in the synovial fluid (SF) of equine joints. Methods-SF was collected from normal and osteoarthritic metacarpophalangeal joints (normal: 14 adult, 28 juvenile; OA: 22 adult). And from normal and osteochondrotic tarsocrural joints (5 months: 11 normal, 8 OC; 11 months: 7 normal, 6 OC). Subsequently, overall MMP activity was measured. Results-The level of active MMPs was alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 7 publications
6
37
1
Order By: Relevance
“…These results are in agreement with the data from Clegg et al [9] who found a rise in MMP-9 activities in a broad range of aseptic joint diseases. In osteoarthritic joints, Brama et al [3] also found the MMP-9 activity was nearly twice as high as in normal joints, but, in OCD joints, MMPs activity was not significantly different from normal control joints. In humans with rheumatoid arthritis, the concentrations of MMP-2 and 9 in synovial fluids do not seem to be influenced by the amount of residual cartilage [13].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with the data from Clegg et al [9] who found a rise in MMP-9 activities in a broad range of aseptic joint diseases. In osteoarthritic joints, Brama et al [3] also found the MMP-9 activity was nearly twice as high as in normal joints, but, in OCD joints, MMPs activity was not significantly different from normal control joints. In humans with rheumatoid arthritis, the concentrations of MMP-2 and 9 in synovial fluids do not seem to be influenced by the amount of residual cartilage [13].…”
Section: Discussionmentioning
confidence: 99%
“…The MMP activity assays were previously shown to be specific for MMP-1, MMP-3 and gelatinolytic activities (MMP-2yMMP-9yMMP-13), respectively (Beekman et al, , 1999Brama et al, 1998;DeGroot et al, 2001) MMPs associated with collagen turnover were extracted from tendon samples using a standardised protocol and normalised against the dry weight of the tendon to enable the comparison of net enzyme activities between specimens; see Fig. 1 and Tables 1 and 2.…”
Section: Mmp Activities In Tendon Extractsmentioning
confidence: 99%
“…Upon cleavage, quenching is lost, and an increase in fluorescence is measured proportional to the amount of hydrolysed substrate (Beekman et al, , 1999. We have designed fluorogenic substrates using fluoresceinyDabcyl as the fluorophoreyquencher combination (Beekman et al, 1999); these substrates are approximately 100-200 times more sensitive than previously used substrates in which EDANSyDabcyl acted as the fluorophorey quencher combination (Beekman et al, , 1999Brama et al, 1998Brama et al, , 2000. We have developed formats in which it is possible to determine MMP-1 (collagenase 1) activity, MMP-3 (stromelysin 1) activity or gelatinolytic (MMP-2, MMP-9 and MMP-13) activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In juvenile horses, stromelysin or matrix metalloproteinase-3 (MMP-3) activity in synovial fluid was demonstrated to be twofold to threefold higher than in synovial fluid of adult horses (Brama et al, 2000), and higher in 5-month-old than in 11-month-old foals. In adult horses, MMP activity of synovial fluid was independent of age but was nearly twofold higher in osteoarthritis (OA) than in normal joints (Brama et al, 1998). In adult horses, a significant increase of gelatinase (MMP-9) activity was found in synovial fluids of osteoarthritic joints with severe cartilage lesions (Jouglin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%